Infection control in dentistry - Nnaji, Chukwuemeka E.; Ime, Akaninyene U.; Nwatu, Jessica C.; Okolo, Paschaline U.; Ochiagha, Clara S.; Nwachukwu, Joy O.; Onyeabor, Heaven C. (Orapuh Journal, 2021)
In a dental clinic setting, patients’ saliva mixed with crevicular fluid, oral deposits, blood, and pus is often splattered and aerosolized. These aerosolized and splattered materials often contain potentially infectious microbes and they cause transmissible diseases. Thus, during dental treatment, both patients and dental health care personnel (DHCP) may be exposed to potentially infectious agents through contact with blood, oral and respiratory secretions, and contaminated instruments and equipment. This paper reviewed some previously published materials and synthesized an up-to-date knowledge status on infection control in dentistry. It also clarified the significance of infection control in the prevention and control of healthcare-associated infections (HAIs) in dental practice. The authors carried out a narrative review of the current status of infection control in dentistry. The process of writing took place over one month, between July 20 and August 20, 2021. During this review, the authors sought relevant works online. They conducted the online literature search using various databases like PubMed, Z-library, Medline, JSTOR, EBSCOhost, and Google scholar and obtained textbooks and articles published in different journals. Google and Edge search engines were used to find the required literature. The authors used keywords such as ’infection control’, ’infection control in dentistry’, ‘infection control measures’, ‘infection control in dental practice’, ‘precautionary measures in infection control’, etc. The authors extracted and documented vital information from the different original articles, textbooks, and paper reviews based on the objectives of this review. Inclusion criteria in the study were bibliographic reviews, systematic reviews, meta-analyses, randomized controlled trials, cohort studies, case reports, and studies in English on the subject matter. The authors excluded articles that were unrelated to the topic, whose full-texts were not available, and that were not in the English Language. The study showed that infection control increases the incidence of successful dental treatment. Also, following the laid down standard precautions and treating all patients as being potentially infectious are the main infection control practices in dentistry.